Women’s Religious Authority and Women’s Empowerment: An Analysis of Muslimah Reformis and Sisters in Islam - Firmanda Taufiq; Iqomah Richtig (DINIKA : Academic Journal of Islamic Studies, 2026)
In recent years, women have played an important role in the context of religious authority in Southeast Asia, especially Indonesia and Malaysia. In addition, women's empowerment has also become one of the priority issues of several Islamic activists, groups, and Muslimah-based Islamic organizations. In this case, two women's Islamic media platforms that are massive in fighting for women's issues, gender equality, and inclusive Islamic discourse, namely Muslimah Reformis and Sisters in Islam. Furthermore, this research explores the role of women's religious authority and women's empowerment in Indonesia and Malaysia through the activism of women Muslimah Reformis (MR) from Indonesia and Sisters in Islam (SIS) from Malaysia. Both focus on fighting for gender equality, and actively voice inclusive Islamic discourse. Through netnography and interviews, this research shows that Muslimah Reformis and Sisters in Islam play an important role as agents of change in women's activism, producing ideas about women's empowerment, and efforts to fight for gender equality. The findings of this study demonstrate that Muslimah Reformis and Sisters in Islam not only serve as platforms for disseminating ideas but also function as instruments for advancing counter-narratives (battle of ideas) within digital spaces at critical moments. Simultaneously, they educate Muslim women that the Quran and hadith Islam’s foundational texts should be interpreted contextually rather than rigidly or literally, thereby preventing adherence to conservative and inflexible ideologies. Together, these organizations reframe Islamic teachings by highlighting their inherent support for gender equality and humanistic values, thereby providing Muslim women with a more inclusive and progressive framework for engaging with modern life.